Dose-related ethanol intake, Cx43 and Nav1.5 remodeling: Exploring insights of altered ventricular conduction and QRS fragmentation in excessive alcohol users. (January 2018) - Hung, Chung-Lieh; Lai, Yu-Jun; Chi, Po-Ching; Chen, Liang-Chia; Tseng, Ya-Ming; Kuo, Jen-Yuan; Lin, Cheng-I; Chen, Yao-Chang; Lin, Shing-Jong; Yeh, Hung-I
Abstract: Background: Chronic, excessive ethanol intake has been linked with various electrical instabilities, conduction disturbances, and even sudden cardiac death, but the underlying cause for the latter is insufficiently delineated. Methods: We studied surface electrocardiography (ECG) in a community-dwelling cohort with moderate-to-heavy daily alcohol intake (grouped as > 90 g/day, ≤ 90 g/day, and nonintake). Results: Compared with nonintake, heavier alcohol users showed markedly widened QRS duration and higher prevalence of QRS fragmentation (64.3%, 50.9%, and 33.7%, respectively, χ 2 12.0, both p < 0.05) on surface ECG across the 3 groups. These findings were successfully recapitulated in 14-week-old C57BL/6 mice that were chronically given a 4% or 6% alcohol diet and showed dose-related slower action potential upstroke, reduced resting membrane potential, and disorganized or decreased intraventricular conduction (all p < 0.05). Immunodetection further revealed increased ventricular collagen I depots with Cx43 downregulation and remodeling, together with clustered and diminished membrane Nav1.5 distribution. Administration of Cx43 blocker (heptanol) and Nav1.5 inhibitor (tetrodotoxin) in the mice each attenuated the suppression ventricular conduction compared with nonintake mice ( p < 0.05). Conclusions: Chronic excessive alcohol ingestion is associated with dose-related phenotypic intraventricular conduction disturbances and QRS fragmentation that can be recapitulated in mice. The mechanisms may involve suppressed gap junction and sodium channel functions, together with enhanced cardiac fibrosis that may contribute to arrhythmogenesis. Highlights: Mouse model of chronic alcohol feeding showed altered ventricular conduction. Dispersed cardiac electrical propagation by optical mapping follows dose-response relationship. Down-regulated Cx43, diminished membrane Nav1.5 expression and ventricular collagen I formation possibly explain this phenomenon. The electrical phenotype of mice recapitulated human findings.